PEMAHAMAN MAHASISWA AKUNTANSI TENTANG MAKNA KONVERGENSI IFRS DI INDONESIA (STUDI KASUS DIPROGDI AKUNTANSI PADA PERGURUAN TINGGI YANG SUDAH TERAKREDITASI A DI KOTA SEMARANG) - Astuti, Ernawati Budi (AKSES: Jurnal Ekonomi dan Bisnis, 2014)
This study aims to determine the student's understanding of the meaning of accounting IFRS convergence in Indonesia and the factors that shape the level of understanding. This study uses primary data where researchers conducted interviews with informants students majoring in accounting at the Faculty of Economics and Business, University of Diponegoro, who has taken courses in Accounting Theory. Intake of students as informants based on reasons that are prospective accountant accounting students who will be entering the world of business as a maker of reliable financial statements. Accounting students must explore and understand the international accounting standards (IFRS) that students will be better prepared to work with the demands of the job that implement global standards and is ready to compete with foreign accountants will be freely worked in Indonesia. Accounting graduates who have a good knowledge of the IFRS will have a competitive advantage when recruiting employees. This study found that the related IFRS convergence process in Indonesia, informants consisting of two different groups, under the guidance of lecturer of different subjects, have different levels of understanding. Informants from Group I have a pretty good understanding, come to understand the level of extrapolation. Despite the novelty of IFRS convergence is often perceived as difficult to understand, but with the support of the direction of professors, books in the library facilities adequate and hotspot networks provided by the campus, making students feel greatly helped to be able to get information about IFRS with ease. Unlike the informant of Group II are visible only to the extent of understanding the translational level. Although they can enjoy the same facilities (books in the library and network hotspot) but lecturer of not giving the opportunity to be more extensive study of IFRS convergence. Keywords: comprehension, Accounting Standards, convergence.